(untitled) (World Bulletin of Education and Learning, 2025)
The ud (Arabic: ʿūd), one of the oldest plucked string instruments in the Near Eastern cultural space, has played a pivotal—yet often underexamined—role in the development of Central Asian musical traditions. In Uzbekistan, particularly within the context of maqom, the ud historically functioned not only as a performance instrument but also as a conceptual and terminological reference point for modes, melodic structures, and pedagogical systems. This article investigates the musical-terminological significance of the ud in Uzbek traditional music, tracing its historical circulation, organological features, integration into maqom practice, and its influence on the theoretical vocabulary of the region. Through comparative analysis of manuscripts, oral histories, and modern ethnomusicological findings, the study argues that the ud served as a formative link between Middle Eastern modal theory and Central Asian maqom aesthetics. The research contributes to a broader understanding of how instrument-based terminology shaped the intellectual foundations of the Uzbek musical canon.